Optimalisasi Penggunaan Bandwidth Voucher Mikhmon Menggunakan Mikrotik Pada BEM FMIPA Universitas Riau - Nazya Fachriah Handayani; Diva Larasaty; Veronika Dwi Deswati Br Sianipar; Doni Saputra; Taufik Wibawa Silalahi; Bagus Tiyogo Yogisworo; Rahmat Hidayat (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The use of computer networks plays an important role in facilitating daily work. Seeing its important role in facilitating work, its needs will continue to increase. Bandwidth management is needed in the use of computer networks, in order to manage the use of network capacity that can be used. Mikrotik as one of the devices that is efficient in monitoring all computer network needs. By using queues as bandwidth management and also mikhmon vouchers, this way network management can be more efficient. The implementation of this network management is highly recommended so that it can be applied to small-scale environmental networks. BEM FMIPA UNRI as a case study place in implementing the application of this problem. BEM FMIPA itself is a place for organizing students of the Faculty of Mathematics and Natural Sciences at the University of Riau. With this research, it aims to provide convenience in managing bandwidth usage using hotspot vouchers. Therefore, the management of the BEM FMIPA UNRI computer network will use the Mikrotik routerboard and Mikhmon as hotspot monitoring that has been configured via Mikrotik.